The Influence of the Reciprocal Teaching Method on Students’ Reading Comprehension of the Recount Texts at an Indonesian Islamic Secondary School - Pramesti, Sevina Putri; Madkur, Ahmad (Borneo Journal of Language and Education, 2026)
This quantitative pre-experimental study examined the influence of Reciprocal Teaching in improving tenth-grade students’ reading comprehension of recount texts among the tenth graders at an Indonesian Islamic Secondary School in the province of Lampung, Indonesia. This research used a one-group pre-test post-test design with 18 students. After the implementation of the Reciprocal Teaching method, a post-test aligned with the four core strategies, namely: predicting, clarifying, questioning, and summarizing, was conducted. The Shapiro-Wilk normality test showed that the pre-test scores were not normally distributed (p-value = .020), while the post-test met the normality assumption (p-value = .139). A Wilcoxon test was then applied and revealed a highly significant improvement (p-value = .000), indicating that Reciprocal Teaching had a strong positive effect on students’ reading comprehension on recount text. The findings conclude that the structured scaffolding provided by RT effectively enhances students' ability to construct meaning and internalize reading strategies. This study highlights the significance of RT as a robust instructional tool for EFL teachers to foster independent reading habits and improve academic outcomes in Islamic secondary school settings. The results recommend broader implementation of strategy-based instruction to address persistent literacy gaps in foreign language learning.